Assessment of food insecurity and its associated factors among adult diabetic patients in Gambella town public hospital, South Western Ethiopia, 2023 - Girma, Zeleke; Teka, Mehari; Misker, Direslgne; Chisha, Yilma; Gujo, Mintesinot Melka; Shibru, Endashew; Wakeyo, Mamud Umer; Timiketu, Lidetu; Toma, Temesgen Mohammed; Haile, Yosef (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionFood insecurity is a multidimensional issue that has been related with poor overall health, obesity and chronic diseases and not only related with increased prevalence of diabetes but also with increasing health care expenses. There is paucity of researches conducted to assess food insecurity and its associated factors among adult diabetic clients in Ethiopia. Hence this study was aimed to assess food insecurity and its associated factors among adult diabetic patients in Gambella town public hospitals.MethodsA facility based cross sectional study was conducted among adult diabetic clients in Gambella town public hospital from May 1 to June 30, 2023. A systematic sampling technique was used to select a sample of 412 patients. Data were collected by trained data collectors using structured questionnaires. Data were checked for its completeness and consistence then entered into Epidata 4.6 and transported to SPSS version 26 for analysis. Bivariate analysis was done to make variables candidate for multivariate analysis at p-value <0.25. In multivariate analysis AOR with 95% CI were used to declare factors associated with food insecurity at p-value <0.05.ResultsThe prevalence of food insecurity was found to be 59.5% (95% CI: 54.6%-64.3%). In multivariate analysis the variables age 18 to 24 years (AOR=0.093,95% CI:0.02-0.30), able to read and write (AOR=4.31, CI:1.246-11.250), employed (AOR=0.20; 95% CI: 0.063-0.63), low wealth status (AOR=3.02, CI:1.265-4.788) OR=2.46, CI:1.265-4.788), medium wealth status (AOR=1.88, CI:1.002-3.815). Family size (AOR=0.48; 95% CI: 0.27-0.87), and family history of diabetes (AOR=2.86, CI: 1.43- 5.72) were significantly associated with food insecurity. income and (AOR=1.88, CI:1.002-3.815)Conclusion and recommendationsThe prevalence of food insecurity among adult diabetic patients was high. Therefore, health professionals should give emphasis to encourage self-management for those who have family history of diabetes in order to screen the clients at early before the occurrence of DM complication and health care expenditure.